4, 6‐Barbaralanedicarboxy‐2, 8‐dicarboxylic anhydride and 1, 5‐dimethyl‐4, 6‐semibullvalenedicarboxy‐2, 8‐dicarboxylic anhydride: examples of unusual barbaralanes and semibullvalenes that do not undergo the Cope rearrangement. They are locked as the closed tautomers†. (10th August 2016) - Williams, Richard Vaughan; Aring, Andrew J.; Bonifacio, Margel C.; Blumenfeld, Alexander; Abe, Manabu; Sheridan, Robert S.
Abstract : Barbaralanes and semibullvalenes are generally fluxional molecules renowned for their exceedingly lowCope rearrangement activation barriers and their close approach to homoaromaticity. The title compounds are unusual in that they do not undergo theCope rearrangement and are locked as a single tautomer with no evidence whatsoever for the existence of the other "open" tautomer. This total lack of theCope rearrangement was demonstrated through variable‐temperature 13 C NMR spectroscopy and computational studies. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Contrary to normal barbaralanes and semibullvalenes, these unusual examples do not undergo the Cope rearrangement and are locked as the sole observable tautomers in the closed form.